Gemella Species Endocarditis in a Child - Laura K Purcell; John P Finley; Robert Chen; Marguerite Lovgren; Scott A Halperin (Canadian Journal of Infectious Diseases)
Organisms of the genus Gemella can, on occasion, cause serious systemic illness. The present paper reports a successfully treated case of endocarditis in a 12-year-old girl with congenital heart disease caused by species of Gemella. The child presented with cough, fatigue and decreased appetite without fever. Echocardiogram demonstrated marked mitral insufficiency with flail posterior mitral valve leaflet, mitral valve vegetations, and an enlarged left atrium and ventricle. While being treated with vancomycin, the child initially had persistent bacteremia, which resolved after the addition of gentamycin; the course of therapy was completed with penicillin G and gentamycin once antimicrobial susceptibilities were available. Attempts to identify the species of Gemella were unsuccessful in the local laboratory, and at reference laboratories in Canada and the United States. The isolate is undergoing further evaluation to determine its taxonomic status.